PENGARUH HUBUNGAN MODAL BANK TERHADAP PENCIPTAAN LIKUDITAS DENGAN TINGKAT LIKUIDITAS DAN RISIKO POLITIK SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Shanghai Stock Exchange dan Tokyo Stock Exhange pada Tahun 2019-2024) - Nanda Fauziyah Qothrunnada; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
The research aims to examine the effect of the relationship between bank capital and liquidity creation, with liquidity levels and political risk acting as moderating variables. The dependent variable in this research is liquidity creation, the independent variable is bank capital, and the moderating variables are liquidity levels and political risk. There are six control variables in this research, namely return on assets, bank efficiency, bank risk, bank size, GDP growth, and inflation rate.The research utilises secondary data from company annual reports that were published in Bloomberg Terminal. Using purposive sampling, 192 samples were obtained comprising the banking sector listed on the Shanghai Stock Exchange and the Tokyo Stock Exchange from 2019 to 2024. The research uses Two-Stage Least Squares (2SLS) analysis and instrumental variables.The results of this study shows that bank capital has a negative effect on liquidity creation, though this is not statistically significant. Furthermore, it was found that liquidity levels negatively moderates and political risk positively moderates the effect of bank capital on liquidity creation.